2024
DOI: 10.3390/toxins16010047
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins-Imprinted Polymers: A State-of-the-Art Review

Simone Cavalera,
Laura Anfossi,
Fabio Di Nardo
et al.

Abstract: Mycotoxins are toxic metabolites of molds which can contaminate food and beverages. Because of their acute and chronic toxicity, they can have harmful effects when ingested or inhaled, posing severe risks to human health. Contemporary analytical methods have the sensitivity required for contamination detection and quantification, but the direct application of these methods on real samples is not straightforward because of matrix complexity, and clean-up and preconcentration steps are needed, more and more requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 128 publications
0
1
0
Order By: Relevance
“…Four absorbents (activated carbon, amorphous graphite, graphitized carbon black, and octadecylsilane) suitable for SPE columns have been evaluated by Prakasham et al [121], who concluded that the best matrix for cleaning samples is activated carbon. However, immunoaffinity columns represent an effective and robust tool for mycotoxin cleanup, but the prediction is that soon, molecularly imprinted polymers will be competitive with immunoaffinity-based materials [128,129].…”
Section: Ota Analytical Methodsmentioning
confidence: 99%
“…Four absorbents (activated carbon, amorphous graphite, graphitized carbon black, and octadecylsilane) suitable for SPE columns have been evaluated by Prakasham et al [121], who concluded that the best matrix for cleaning samples is activated carbon. However, immunoaffinity columns represent an effective and robust tool for mycotoxin cleanup, but the prediction is that soon, molecularly imprinted polymers will be competitive with immunoaffinity-based materials [128,129].…”
Section: Ota Analytical Methodsmentioning
confidence: 99%